2022
DOI: 10.3389/fpsyt.2022.870984
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Related Psychosocial Care in General Hospitals: Results of an Online Survey of Psychosomatic, Psychiatric, and Psychological Consultation and Liaison Services in Germany, Austria, and Switzerland

Abstract: BackgroundThe coronavirus disease 2019 (COVID-19) pandemic was accompanied by new challenges for psychosocial health care to enable the support of affected patients, their families, and staff in general hospitals. In this study, we aimed to describe the structures and procedures put in place by psychosomatic, psychiatric, and psychological consultation and liaison (CL) services in German, Austrian, and Swiss general hospitals, and to elucidate the emerging needs for cooperation, networking, and improvement.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Patients with an ethnic minority background and patients experiencing psychological distress at the time of admission may be particularly vulnerable to negative long-term psychological effects of COVID-19 [ 54 ]. The provision of staff guidelines for COVID-19 patients, e.g., protocols for screening for symptoms of anxiety, may help healthcare professionals identify and support patients who experience psychological distress during admission [ 55 ]. Ongoing and future studies will hopefully provide more robust knowledge about validated psychological support interventions that may be suitable for implementation during and following a hospitalization with COVID-19-related illness.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with an ethnic minority background and patients experiencing psychological distress at the time of admission may be particularly vulnerable to negative long-term psychological effects of COVID-19 [ 54 ]. The provision of staff guidelines for COVID-19 patients, e.g., protocols for screening for symptoms of anxiety, may help healthcare professionals identify and support patients who experience psychological distress during admission [ 55 ]. Ongoing and future studies will hopefully provide more robust knowledge about validated psychological support interventions that may be suitable for implementation during and following a hospitalization with COVID-19-related illness.…”
Section: Discussionmentioning
confidence: 99%
“…Resilience is the ability of an individual to respond to stress and adversity in an adaptive way such that goals are achieved at minimal psychological and physical costs and mental well-being rapidly ”bounces back” [ 1 ]. As resilience can counteract negative effects of workplace stress, the concept of physician resilience has emerged in response to high prevalence rates of physician burnout and physician stress [ 2 – 4 ], which seem to have substantially increased during the COVID-19 pandemic [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Resilience is the ability of an individual to respond to stress and adversity in an adaptive way such that goals are achieved at minimal psychological and physical costs and mental well-being rapidly "bounces back" [1]. As resilience can counteract negative effects of workplace stress, the concept of physician resilience has emerged in response to high prevalence rates of physician burnout and physician stress [2][3][4], which seem to have substantially increased during the COVID-19 pandemic [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…during the COVID-19 pandemic[6,7]. More speci cally, we looked at whether and, if so, to what extent resilience and postgraduate training in psychosomatic medicine in Austria were related to perceived quality of care and to further indicators of health care quality, i.e., professional autonomy, adequate time for patient care, and job satisfaction.We found that both resilience and training level in psychosomatic medicine separately predicted perceived quality of delivered care when controlling for age, gender, number of patients, treatment of COVID-19 patients, own health concerns, nancial strains, as well as training and resilience as control variables.…”
mentioning
confidence: 99%